Transitioning from Early Childhood Education to Elementary School: Holistic Readiness Without Formal Reading, Writing, and Arithmetic Instruction - Gde Putu Arya Oka (Universitas Pendidikan Ganesha, 2026)
This study is grounded in the importance of strengthening the transition from early childhood education to primary school to support children’s holistic and joyful learning readiness. However, its implementation still faces challenges in literacy-numeracy learning consistency, teaching strategies, and parental involvement. This study aimed to analyze the implementation of the ECE-to-Elementary School transition strengthening movement through the perceptions of kindergarten teachers, principals, elementary school teachers, and parents regarding the implementation of the government-initiated transition program. This study employed a qualitative approach with a descriptive method. The research subjects consisted of kindergarten teachers, school principals, elementary school teachers, and parents. Data were collected through interviews, observations, and documentation. Data analysis used the interactive model of Miles and Huberman supported by Nvivo software to assist the processes of data reduction, data display, and conclusion drawing. The findings show that literacy and numeracy implementation in early childhood education has not been fully consistent, as some institutions still introduce reading, writing, and arithmetic through play-based approaches. Meanwhile, primary schools have removed literacy and numeracy tests from new student admissions and have begun creating more enjoyable learning environments. This study concludes that the PAUD-to-primary school transition program has been implemented, but not yet optimally, particularly in terms of parental involvement and consistency in transition-based learning. The implications highlight the need to strengthen school-parent collaboration and develop more adaptive, child-centered transition learning strategies.